How to achieve sustainable operation of transport infrastructure development: a case study of 30 transport infrastructure projects in China - Jie Chen; Chongsen Ma (Archives of Civil Engineering, 2024)
Transport infrastructure projects are distinguished by their high levels of investment, lengthy construction periods, and reliance on government subsidies during operation. These factors have far-reaching impacts, not only on the sustainable operation and success of the projects themselves, but also on the orderly functioning of society and the sustainable development of the economy. As such, it is of paramount importance to thoroughly investigate the sustainable operation of transport infrastructure. This paper examines the impact of sustainable operation on transport infrastructure by analysing 30 projects in China’s transport infrastructure sector. The study employs the qualitative comparative analysis method. To achieve the aim of this paper, we identified five dimensions for assessing a project’s sustainability. These include the economic environment of the construction site, operational market demand, government support capacity, and enterprise management level. This analysis offers valuable guidance for future engineering projects. Finally, the study identified seven strategies for achieving sustainable operation of the project. The findings revealed that the economic development status, population size, and government subsidies of the construction site do not effectively promote sustainable operation of the project. Rather, they can hinder enterprises’ market competitiveness. The study’s results can assist decision-makers in determining the feasibility of implementing sustainable management practices in the new project. Examine the factors that influence the achievement of sustainable business while enhancing the operational efficiency of ongoing initiatives. This research aims to produce a valuable addition to risk assessments in sustainable operation research and the advancement of transportation infrastructure reduction.